Upgrading of diols by gas-phase dehydrogenation and dehydration reactions on bifunctional Cu-based oxides - Torresi, Pablo Antonio (2014)
Biomass-derived short chain polyols can be transformed in valuable oxygenates used as building blocks. The gas phase conversion of a model molecule of 1,3-diols (1,3-butanediol) was studied on bifunctional Cu-Mg, Cu-Al and Cu-Mg-Al mixed oxide catalysts that combine surface Cu0 particles and acid-base properties. A series of ZCuMgAl catalysts (Z=0.3-61.2 wt.% Cu, Mg/Al=1.5 molar ratio) was prepared by coprecipitation and thoroughly characterized by several techniques such as BET surface area, TPR-N2O chemisorption, XRD and TPD of CO2. The ZCuMgAl catalysts promote the upgrading of the diol by a series of dehydrogenation and/or dehydration reactions proceeding at reaction rates that depend on the copper content (Z). The overall activity increases linearly with the amount of surface Cu0 species thereby confirming participation of metallic sites in rate-limiting steps. Besides, surface Cu0 sites favor the reaction pathway toward 1,3-butanediol dehydrogenation. Thus, the dehydrogenation/dehydration selectivity ratio increases with Z as a result of the enhanced amount of exposed Cu0 particles. ZCuMgAl catalysts with Z < 8wt.% dehydrogenate-dehydrate-hydrogenate the diol at low rates giving mainly C4 ketones and break the intermediates forming C1-C3 oxygenates; catalysts with Z > 8wt.% are more active and yield valuable multifunctional C4 oxygenates such as hydroxyketones and to a lesser extent, unsaturated alcohols and ketones. A strongly basic Cu-Mg catalyst promotes the C-C bond cleavage reaction giving short carbon chain oxygenates at low rates; an acidic Cu-Al catalyst converts the diol into the C4 saturated ketone and olefins.